Access to healthcare in superdiverse neighbourhoods - Pemberton, S.; Phillimore, J.; Bradby, H.; Padilla, B.; Lopes, J.; Samerski, S.; Humphris, R. (Health and Place, 2019)
To date little attention has been focused on how the differing features of ‘superdiverse’ neighbourhoods shape residents’ access to healthcare services. Through utilising a cross-national mixed-methods approach, the paper highlights how defining features of superdiverse neighbourhoods - ‘newness’ ‘novelty’ and ‘diversity’ - influence a number of neighbourhood ‘domains’ and ‘rules of access’ that regulate access to healthcare. Issues of uncertainty, affordability, compliance, transnationalism and the diversity of community and local sociability are identified as being particularly significant, but which may vary in importance according to the nationality, ethnicity and / or religion of particular individuals.